A univariate rational quadratic trigonometric interpolating spline to visualize shaped data - Bashir, Uzma; Jamaludin Md. Ali, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study was concerned with shape preserving interpolation of 2D data. A piecewise C1 univariate rational quadratic trigonometric spline including three positive parameters was devised to produce a shaped interpolant for given shaped data. Positive and monotone curve interpolation schemes were presented to sustain the respective shape features of data. Each scheme was tested for plentiful shaped data sets to substantiate the assertion made in their construction. Moreover, these schemes were compared with conventional shape preserving rational quadratic splines to demonstrate the usefulness of their construction.